Analisis Gradien Sebaran Air Tanah Berdasarkan Elevasi Muka Air Tanah di Kecamatan Ternate Utara, Kota Ternate - Yanny, Yanny; Conoras, Wawan AK; Rambaen, Adelheit (Universitas Pattimura, 2025)
The availability of groundwater in the North Ternate District plays an important role in meeting domestic and industrial needs amidst the challenges of reduced water resources due to land conversion into built-up areas and reducing water catchment areas. This study aims to analyze the distribution pattern of groundwater levels to identify recharge and discharge areas and their application in water resource management in the region. The research method includes field surveys to collect data, including coordinate points, well topographic elevation data, well water depth, and well height, as well as mapping using Surfer software to produce spatial visualization of groundwater flow patterns. The results of the study showed that the highest groundwater level elevation ranged from 40-60 masl, which was concentrated in Soa-Sio Village and acted as a recharge zone, while the discharge zone has a low groundwater level elevation (<10 masl), which was concentrated in Sangaji and Dufa-dufa Villages, where excessive groundwater exploitation occurs and there was the potential for seawater intrusion. The results of this study are expected to provide information and a basis for policy regarding the importance of protecting catchment areas through sustainable land use management and controlling groundwater utilization to prevent depletion and decline in groundwater quality.